Studies on the Shape Change in Rabbit Platelets Induced by Adenosine Diphosphate or Several Metabolic Inhibitors - Kobayashi, Norio; Maekawa, Tadashi (Thrombosis and Haemostasis, 1974)
1. The shape change of platelet was induced in vitro by an addition of ADP, NEM, KCN or distilled water. The change induced by ADP occurred very rapidly.2. Among these reagents, only ADP induced the platelet aggregation.3. When ADP was added before the completion of the shape change by NEM, the shape change by ADP took place, while both ADP and NEM were added simultaneously, the pattern of the shape change was similar to that of ADP alone.4. The shape change of platelet by ADP was inhibited by the previous addition of adenosine, which did not affect the shape change induced by NEM.5. Correlation of the shape change of platelets to their aggregation was discussed.